Pengembangan Thesaurus On-Line sebagai Electronic Performance Supporting System dalam Perkuliahan Teknologi Jaringan Jurusan Teknologi Pendidikan Universitas Negeri Malang Tahun Akademik 2012/2013 - Yulias Prihatmoko; Zainul Abidin; Yerry Soepriyanto (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2018)
Lectures for the network technology subject at the Department of Educational Technology (TEP), State University of Malang have been supported by printed teaching materials that have been adapted to the characteristics of TEP students. Printed teaching materials are supported by an on-line thesaurus as an electronic performance supporting system that supports students in interpreting difficult words found in printed teaching materials. The Borg & Gall development model was adapted for development. The development produces an on-line thesaurus based on data analysis from 1 media expert, 1 material expert and the effectiveness of learning outcomes in the limited field test meets the valid criteria, with the results of the calculation of media experts 94.64%. On-line thesaurus material experts 78.33%. There is an increase in learning outcomes in limited trials between before and after the use of media with an average difference in value of 24.375